Identifying The Extent Of Religiosity, Risk, And Socio-Demographic Factors In Selecting To Invest In Islamic Unit Trust - Ab Shukor, Suraya (2009)
This paper's main area of study is the behaviour of the financial products customers especially the Islamic financial products, specifically the Islamic unit trust in the Malaysian market.